Artificial intelligence between supporting and weakening judicial evidence in courts (The International Journal for Scientific Research, 2026)
The acceptance of forensic evidence is the result of fair competition between the parties in a legal case; it's the foundation upon which a judge relies to issue rulings. When evidence is strong and unquestionable, the judge can confidently accept it, trusting their sound judgment in building their judicial conviction and issuing their rulings.With technological advancements, especially the powerful rise of artificial intelligence (AI), government agencies and institutions have rapidly moved to embrace this progress. This is clear in the shift by criminal investigation agencies toward using modern techniques to uncover and present correct evidence more easily and effectively. Courtrooms have also seen a notable transformation in the means of proof, using unconventional methods to solve complex cases. These methods include technologies for identifying people through voice, hand, and eye prints, as well as facial recognition. Additionally, they use DNA technology to trace the origin of liquids and biological tissues.However, as much as AI has become a positive tool for assisting criminal investigation agencies in obtaining sound forensic evidence, it is not without risks. These dangers lie in the immense potential of AI to create fabricated evidence. This includes documents and photos used to prove or disprove a person's presence at a specific time and place. It also involves audio and visual evidence where the average person struggles to distinguish between what's real and what's fake.The use of such fabricated evidence can mislead the justice system and may profoundly influence judges as they exercise their natural freedom in issuing rulings. This situation poses a challenge, requiring justice authorities to do their utmost to prevent malicious uses of AI that could subvert justice. This reality places the burden on investigators and judges to gain the knowledge needed for cases where evidence might be altered with AI, thereby avoiding corrupted evidence that would harm justice.
Keywords: Judicial Evidence; Artificial Evidence; Misrepresenting Justice